Efektivitas Ekstrak Daun Sirih (Piper betle L) dan Ekstrak Bawang Putih (Allium sativum) terhadap Mortalitas Larva Nyamuk Aedes aegypti - Amirullah, Amirullah; Malik, Nurhayu; Rosmaya, Rosmaya (Fakultas MIPA UNM, 2019)
Abstract. The study of the efficacy of betel leaf extract (Piper betle L.) and garlic extract (Allium sativum) on the mortality of Aedes aegypti mosquito larvae was carried out at the Zoology Laboratory of the Faculty of Mathematics and Natural Sciences, Halu Oleo Kendari University. Aedes aegypti mosquito larvae were obtained from the rearing of F2 from Aedes aegypti eggs that were taken by ovitrap from in Kambu Village, Kendari City, which is an endemic area of Dengue Hemorrhagic Fever (DHF). Extrac of betel leaf (Piper betle L.) and garlic extract (Allium sativum) at concentrations of 1.0%, 2.0% and 3.0% respectively and their combinations were given to Aedes aegypti larvae (L4). The results showed that the highest larval mortality (88%) occurred after 24 hours of exposure to betel leaf extract (Piper betle L.) at a concentration of 3%, whereas with garlic extract (Allium sativum) the highest larval mortality (98%) occurred at concentration 3 %, and for the highest larval mortality (99%) found in a combination of 3% betel leaf extract (Piper betle L.) and 3% garlic extract (Allium sativum). Based on WHO (2009), the most effective treatment for killing Aedes aegyti larvae is 3% garlic (Allium sativum) extract and a combination of 3% betel leaf extract (Piper betle L.) and 3% garlic extract (Allium sativum).Keywords: Â Biopesticide, Mortality, Aedes aegypti, betle leaf (Piper betle L.), garlic (Allium sativum).